2009
DOI: 10.1007/s00417-009-1177-4
|View full text |Cite
|
Sign up to set email alerts
|

A comparative clinical study of the visual results between three types of multifocal lenses

Abstract: The implantation of tested multifocal intraocular lenses provides good near and distance visual acuity. We did not observe any statistically significant differences between the tested multifocal intraocular lenses with regard to best-corrected distance visual acuity, presence of glare and halo, as well as satisfaction with vision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 19 publications
(16 reference statements)
3
17
0
Order By: Relevance
“…These results are comparable to published results with diffractive multifocal IOL implantation [1,16,17]. The mean of near preferred distance was 24-26 cm.…”
Section: Discussionsupporting
confidence: 94%
“…These results are comparable to published results with diffractive multifocal IOL implantation [1,16,17]. The mean of near preferred distance was 24-26 cm.…”
Section: Discussionsupporting
confidence: 94%
“…General patient satisfaction was very high and stable, with most of patients scoring their level of satisfaction at between 8 and 10 (0 = not satisfied at all and 10 = completely satisfied), as reported for a previous model of the Tecnis diffractive IOL [21]. The VF-14 test detected only slight to moderate difficulty in driving at night.…”
Section: Discussionsupporting
confidence: 70%
“…Additionally, contrast sensitivity was higher in eyes with the ZM900 than in eyes with refractive IOLs or other diffractive multifocal IOLs. 18 Another study also demonstrated that eyes with the ZM900 had better mesopic contrast sensitivity than eyes with refractive multifocal IOLs. 19 Eyes with the ZMB00, a 1-piece acrylic multifocal IOL, had even better contrast sensitivity than eyes with the ZM900 over a shorter time period than eyes with the ZM900.…”
Section: Previous Studies Have Shown That Patientsmentioning
confidence: 97%